Modèle d’estimation de l’élasticité de substitution et du progrès technologique - Zind, Richard (L'Actualité économique, 1981)
ABSTRACTWe derive in the present study a set of equations that yield, through regression analysis, estimates of the elasticity of substitution and of the indexes of technical change attributed to Hicks, Harrod and Solow. On the basis of data drawn from the U.S. non-farm economy, we obtain estimates that are consistent with other findings namely a value for the elasticity of substitution (between labour and capital) that is less than unity and indexes which imply that technology has tended to be Hicks labour-saving, Harrod capital-saving and Solow labour-saving.